Successful ventricular tachycardia radioablation in a patient with previous chemical pleurodesis: A case report - Pavone, Chiara; Scacciavillani, Roberto; Narducci, Maria Lucia; Cellini, Francesco; Pelargonio, Gemma; Bencardino, Gianluigi; Perna, Francesco; Spera, Francesco; Pinnacchio, Gaetano; Sanna, Tommaso; Valentini, Vincenzo; Crea, Filippo (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Stereotactic arrhythmia radioablation (STAR) is a novel technique for the ablation of ventricular tachycardia in patients with contraindications to standard procedures, i.e. radiofrequency ablation. Case presentation: We report the case of a 73-year-old man with nonischemic dilated cardiomyopathy and recurrent VT episodes. Electroanatomic mapping showed VT prevalently of epicardial origin, but direct epicardial access through subxyphoid puncture could not be performed due to pleuropericardial adhesions from a past history of chemical pleurodesis. STAR was performed, with no VT recurrence at follow-up. Conclusions: Previous experiences with STAR mainly focused on its application in frail end-stage heart failure subjects. Our case report demonstrates the importance of STAR as a second choice in patients with unfavorable VT anatomical locations and technical limitations to an optimal radiofrequency ablation. Moreover, it highlights STAR’s effectiveness in the ablation of complex transmural lesions.